Biomaterials in Architecture, and Biomimicry Principles, as Tools for Envisioning the Sustainable Cities of the Future - Christine Dikou (Emerging Issues in Environment, Geography and Earth Science Vol. 2, 2023)
It is widely acknowledged that the impact of human activities on the Earth’s atmosphere following the first industrial revolution was so significant that it was designated as a new geological epoch with the term "Anthropocene." The search for a new design strategy that integrates the nature of urban landscapes with their architecture is critical in the Anthropocene age. Modern instances of green cities and smart cities are the direct result of the emergence of a value system with a highly aesthetic view of global ecosystems, prompting us to seek a non-anthropocentric method of reasoning and, as a result, planning. In this study, we present innovative city design that controls environmental factors and is based on urban planning of cities approached by the principles of biomimicry. The research question is whether natural materials with modern construction methods and biomimicry principles can lead to the design of cities that face the numerous challenges of climate change. Three examples of cities that have adopted the model of biomimicry design principles will be presented, (the city of Lavasa in India, Rocinha favela in Rio de Janeiro, and an industrial ecosystem in the Danish city of Kalundborg), in parallel with a literature review of natural materials. Conclusions will be drawn which will be followed by the formulation of proposals for the optimal planning of cities in terms of sustainability. The goal is to develop a design process targeted at the efficient design of cities in response to climate change.